Large displacement theory of thin-walled curved members and its application to lateral-torsional buckling analysis of circular arches - Koh, Soy Yeo; Usami, Tsutomu; Pama, Ricardo P.; Pichai Nimityongskul; Royal Dutch Government (Bangkok : Asian Institute of Technology, 1978)
The purpose of this study is to establish a one dimensional large displacement theory for curved members with thin-walled open sections. Consequently, this theory is applied in the analysis of lateral-torsional buckling of circular arches. Typical numerical example is shown herein to illustrate how the ratio of different types of rigidities in the non dimensional form affects the buckling loads.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Structures, Theory of; Buckling (Mechanics); Arches